Community Participation in Community Education: A Study at PKBM Geger Sunten, West Bandung Regency - Mulyono, Dinno; Sintiawati, Nani; Widiastuti, Novi (Journal Of Educational Experts (JEE), 2025)
Community participation is a key factor in the success of community education, especially in non-formal education units such as Community Learning Centers (PKBM). This study aims to analyze the level, form, and factors that influence community participation in the implementation of community education at the Geger Sunten PKBM, Suntenjaya Village, Lembang District, West Bandung Regency. The study uses a mixed method approach with a sequential explanatory design. Quantitative data were obtained through questionnaires administered to 45 learners, while qualitative data were collected through in-depth interviews, observations, and documentation. The results show that the level of community participation is in the medium to high category, with participation predominantly occurring at the program implementation stage. The main factors influencing participation include program relevance, management leadership, and community social support. Qualitative findings reinforce that participation is not yet fully substantive because involvement in planning and evaluation is still limited. This study concludes that strengthening community participation requires empowerment strategies based on local needs and a sustainable collaborative approach.